2007
DOI: 10.1375/twin.10.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of Low Mathematics Performance and Normal Variation in Twins from 7 to 9 Years

Abstract: A previous publication reported the etiology of mathematics performance in 7-year-old twins (Oliver et al., 2004). As part of the same longitudinal study we investigated low mathematics performance and normal variation in a representative United Kingdom sample of 1713 same-sex 9-year-old twins based on teacher-assessed National Curriculum standards. Univariate individual differences and DeFries-Fulker extremes analyses were performed. Similar to our results at 7 years, all mathematics scores at 9 years showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…Again, we calculated a composite math score, which was the mean of the three scales. Further information about NC teacher reports as used in TEDS can be found elsewhere (Haworth, Kovas, Petrill, & Plomin, 2007; Kovas et al, 2007; Walker, Petrill, Spinath, & Plomin, 2004;).…”
Section: Methodsmentioning
confidence: 99%
“…Again, we calculated a composite math score, which was the mean of the three scales. Further information about NC teacher reports as used in TEDS can be found elsewhere (Haworth, Kovas, Petrill, & Plomin, 2007; Kovas et al, 2007; Walker, Petrill, Spinath, & Plomin, 2004;).…”
Section: Methodsmentioning
confidence: 99%
“…Results have suggested that mathematics has moderate genetic influences (Hart et al, 2009; Haworth et al, 2007; Haworth et al, 2009; Knopik & DeFries, 1999; Thompson, Detterman, & Plomin, 1991; Wadsworth, DeFries, Fulker, & Plomin, 1995). There is also some evidence of significant shared environmental influences (factors that make twins within the same family similar, but different between families; Hart et al, 2009; Petrill et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted examining genetic and environmental influences on both specific cognitive abilities and general intelligence throughout the lifespan (Finkel et al 1995; Haworth et al 2007; McClearn et al 1997; McGue and Christensen 2002; McGue and Christensen 2001; Oliver and Plomin 2007; Petrill et al 1995; Plomin et al 1994; Polderman et al 2006; Posthuma et al 2000; Read et al 2006; Thapar et al 1994). Consensus in the field of behavioral genetics maintains that hereditary influences account for a substantial proportion of the variance in most cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%